Anatomical and histopathological evaluation of the equine jejunal anastomosis coated with bovine pericardium xenograft - Aguilar G., Ceesar N. (2018)
The evaluation of the untreated bovine pericardium xenograft as a biomaterial for the lining of the small intestine anastomosis in equines was conducted. Seven horses with ages between 3 and 10 years were operated on. Two of them were randomly selected, doing a laparotomy to one of them at 15 days and the other at 100 days post-surgery. In the macroscopic and histopathological studies of the cicatricial area of the end-to-end anastomosis it was evidenced that the xenograft does not contract or move from the line of suture, guaranteeing the process of cicatricial remodeling and avoiding complications such as peritonitis, stenosis, abscesses, anastomotic leakage and adhesions. It is concluded that the untreated bovine pericardium xenograft is viable and effective as a jejunal enterectomy lining, showing good adaptability as a natural microenvironment for progenitor cells responsible for cicatricial remodeling, although it leads to a moderate phlogosis and fibrosis that disappear progressively after the convalescence period, without calcification or collagen degeneration.